(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Foreign body ingestion is frequently encountered in emergency surgical practice. While most cases occur accidentally in children, deliberate ingestion of sharp metallic foreign bodies in mentally competent adults without psychiatric illness is uncommon and poorly described. Sharp metallic objects carry a high risk of gastrointestinal perforation, obstruction, abscess formation, and peritonitis, requiring individualised management. Methods: This retrospective case series included ten consecutive mentally competent young adults presenting with deliberate ingestion of sharp metallic foreign bodies between January 2017 and June 2018. Demographic characteristics, clinical presentation, radiological findings, treatment, operative details, and outcomes were analysed. Results: Ten male patients aged 18–23 years were included. Eight patients (80%) had ingested sewing needles, one (10%) had swallowed a metallic clip, and one (10%) had ingested another sharp metallic object. Abdominal pain was the most frequent presenting complaint (60%), while two patients remained asymptomatic. Plain abdominal radiography accurately localised the foreign body in all patients. Eight patients (80%) were managed conservatively with serial clinical assessment and radiographic follow-up, resulting in spontaneous passage of the foreign body. Two patients (20%) developed perforation peritonitis requiring exploratory laparotomy and successful retrieval of the foreign body. There was no mortality, no major postoperative morbidity, and all patients achieved complete recovery. Conclusion: Deliberate ingestion of sharp metallic foreign bodies in mentally competent young adults is uncommon but may result in life-threatening complications. Careful clinical observation, serial radiographic monitoring, and timely surgical intervention are essential for successful management. Although most patients can be managed conservatively, prompt operative treatment is warranted in those who develop perforation or generalised peritonitis.